Transcriptomic Profiling of In Vitro Tumor-Stromal Cell Paracrine Crosstalk Identifies Involvement of the Integrin Signaling Pathway in the Pathogenesis of Mesenteric Fibrosis in Human Small Intestinal Neuroendocrine Neoplasms - Laskaratos, Faidon-Marios; Levi, Ana; Schwach, Gert; Pfragner, Roswitha; Hall, Andrew; Xia, Dong; von Stempel, Conrad; Bretherton, Josephine; Thanapirom, Kessarin; Alexander, Sarah; Ogunbiyi, Olagunju; Watkins, Jennifer; et al. (Frontiers in Oncology, 2021)
Aim: Analysis of the pathophysiology of mesenteric fibrosis (MF) in small intestinal neuroendocrine tumours (SI-NETs) in an in vitro paracrine model and in human SI-NET tissue samples. Methods: An indirect co-culture model of SI-NET cells KRJ-I and P-STS with stromal cells HEK293 was designed to evaluate the paracrine effects on cell metabolic activity, gene expression by RT2 PCR Profilers to analyse cancer and fibrosis related genes, and RNA sequencing. The integrin signalling pathway, a specific Ingenuity enriched pathway, was further explored in a cohort of human SI-NET tissues by performing protein analysis and immunohistochemistry. Results: RT Profiler array analysis demonstrated several genes to be significantly up- or down-regulated in a cell specific manner as a result of the paracrine effect. This was further confirmed by employing RNA sequencing revealing multiple signalling pathways involved in carcinogenesis and fibrogenesis that were significantly affected in these cell lines. A significant upregulation in the expression of various integrin pathway – related genes was identified in the mesenteric mass of fibrotic SI-NET as confirmed by RT-qPCR and immunohistochemistry. Protein analysis demonstrated downstream activation of the MAPK and mTOR pathways in some patients with fibrotic SI-NETs. Conclusion: This study has provided the first comprehensive analysis of the crosstalk of SI-NET cells with stromal cells. A novel pathway – the integrin pathway – was identified and further validated and confirmed in a cohort of human SI-NET tissue featured by a dual role in fibrogenesis/carcinogenesis within the neoplastic fibrotic microenvironment.